Role of nutrients and mTOR signaling in the regulation of pancreatic progenitors development - Lynda Elghazi; Manuel Blandino-Rosano; Emilyn Alejandro; Corentin Cras-Méneur; Ernesto Bernal-Mizrachi (Elsevier, 2017)
Objective: Poor fetal nutrition increases the risk of type 2 diabetes in the offspring at least in part by reduced embryonic β-cell growth and impaired function. However, it is not entirely clear how fetal nutrients and growth factors impact β-cells during development to alter glucose homeostasis and metabolism later in life. The current experiments aimed to test the impact of fetal nutrients and growth factors on endocrine development and how these signals acting on mTOR signaling regulate β-cell mass and glucose homeostasis. Method: Pancreatic rudiments in culture were used to study the role of glucose, growth factors, and amino acids on β-cell development. The number and proliferation of pancreatic and endocrine progenitor were assessed in the presence or absence of rapamycin. The impact of mTOR signaling in vivo on pancreas development and glucose homeostasis was assessed in models deficient for mTOR or Raptor in Pdx1 expressing pancreatic progenitors. Results: We found that amino acid concentrations, and leucine in particular, enhance the number of pancreatic and endocrine progenitors and are essential for growth factor induced proliferation. Rapamycin, an mTORC1 complex inhibitor, reduced the number and proliferation of pancreatic and endocrine progenitors. Mice lacking mTOR in pancreatic progenitors exhibited hyperglycemia in neonates, hypoinsulinemia and pancreatic agenesis/hypoplasia with pancreas rudiments containing ductal structures lacking differentiated acinar and endocrine cells. In addition, loss of mTORC1 by deletion of raptor in pancreatic progenitors reduced pancreas size with reduced number of β-cells. Conclusion: Together, these results suggest that amino acids concentrations and in particular leucine modulates growth responses of pancreatic and endocrine progenitors and that mTOR signaling is critical for these responses. Inactivation of mTOR and raptor in pancreatic progenitors suggested that alterations in some of the components of this pathway during development could be a cause of pancreatic agenesis/hypoplasia and hyperglycemia. Keywords: Nutrients, mTOR, Rapamycin, Pancreas, Development, Islets, β-cells